2017
DOI: 10.1007/s00394-017-1583-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of food consumption and nutrient intake assessed with three dietary assessment methods: results of the German National Nutrition Survey II

Abstract: Purpose Comparison of food consumption, nutrient intake and underreporting of diet history interviews, 24-h recalls and weighed food records to gain further insight into specific strength and limitations of each method and to support the choice of the adequate dietary assessment method. Methods For 677 participants (14-80 years) of the German National Nutrition Survey II confidence intervals for food consumption and nutrient intake were calculated on basis of bootstrapping samples, Cohen's d for the relevance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…Looking at the estimates of dietary intakes obtained by both methods, some differences can be found. In general, both methods provided, to some extent, results comparable to other studies [16,17,43,44]. The mean dietary intakes obtained with the web-based 24HDR significantly correlate with those obtained with the WFR method.…”
Section: Discussionsupporting
confidence: 84%
“…Looking at the estimates of dietary intakes obtained by both methods, some differences can be found. In general, both methods provided, to some extent, results comparable to other studies [16,17,43,44]. The mean dietary intakes obtained with the web-based 24HDR significantly correlate with those obtained with the WFR method.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, the German National Nutrition Survey II used interviews of diet history to show that older people consumed less meat than younger adults – although here meat referred to all meat types except for fish (Heuer et al , ). It is worth noting that interviews of diet history were found to corroborate other dietary assessment methods within this same previous survey (Straβburg et al , ). While the increased worldwide population is expected to compensate for these trends and supports an annual projected increase in beef and lamb consumption – with most of the gains expected within Asian, African, South American and Oceanian markets (FAO, ) – it would be prudent to consider the demands and requirements of red meat products from elderly people.…”
Section: Market Specifics For Elderly Consumerssupporting
confidence: 72%
“…The results of the National Consumption Survey II showed that the daily vitamin D intake of > 96% of girls and 86% of boys aged 14-18 years failed to meet the recommendations [9,10]. A recent European study, which collected data on the 25(OH)D status of 1006 adolescents aged between 12.5 and 17.5 years, showed that 39% of them had an inadequate vitamin D status (25(OH)D: 20-30 ng/mL), 27% a vitamin D deficiency, and 15% a severe vitamin D deficiency.…”
Section: Foodmentioning
confidence: 99%
“…memory, attention) and scholastic performance (e.g. reading, spelling) in schoolchildren taking regular supplements of DHA and EPA [10][11][12].…”
Section: B Vitamins and A Healthy Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation